1999
DOI: 10.1023/a:1021954402840
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Research has linked language delays in young children to behavior problems and risk for psychopathology. We hypothesized that low language skill would affect normal socialization of emotion regulation, which in turn would affect the development of behavior problems. Seventy-eight mother/preschool-age child pairs participated in two mildly frustrating situations. Parents of children with low verbal comprehension used more unexplained compliance demands than other parents. Further, children whose parents used mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 12 publications
2
21
0
1
Order By: Relevance
“…A growing body of research suggests that children's gender might be particularly influential in eliciting certain control strategies from their caregivers (Stansbury & Zimmerman, 1999). A study of Israeli fathers and their two-year-olds found that fathers exhibited more warm control strategies with their daughters than their sons (Feldman & Klein, 2003), suggesting boys may elicit different control strategies from their fathers than girls.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research suggests that children's gender might be particularly influential in eliciting certain control strategies from their caregivers (Stansbury & Zimmerman, 1999). A study of Israeli fathers and their two-year-olds found that fathers exhibited more warm control strategies with their daughters than their sons (Feldman & Klein, 2003), suggesting boys may elicit different control strategies from their fathers than girls.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Children's language skills have also been linked to differential parenting (Tamis-LeMonda, Briggs, McClowry, & Snow, 2009). For example, a study of mothers and their preschool aged children found that children with lower verbal comprehension had mothers who used more unexplained compliance demands with their toddlers (Stansbury & Zimmerman, 1999). Additional findings suggest that children's early language skills are linked with their regulatory skill development (Vallotton & Ayoub, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with these skills are able to monitor, evaluate and modify emotional reactions (Thompson 1994), or in other words, to manage the ebb and flow of negative emotions (Kopp 1989). The ability to regulate emotions effectively is crucial to successful development (Morris et al 2007) and is associated with social competence while difficulties with emotion regulation are linked to both internalizing and externalizing disorders (Stansbury and Zimmermann 1999; Zeman et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…This chapter has drawn from the 2000 Earth Search report (Saltus et al 2000), from a report prepared for the Young-Sanders Center by Roland Stansbury (Stansbury 1999) and from newly collected data.…”
Section: The Sidewheel Steamboat Gray Cloud or Uss Col Kinsmanmentioning
confidence: 99%